2017
DOI: 10.1080/15592294.2017.1385685
|View full text |Cite
|
Sign up to set email alerts
|

SETDB2 and RIOX2 are differentially expressed among renal cell tumor subtypes, associating with prognosis and metastization

Abstract: Increasing detection of small renal masses by imaging techniques entails the need for accurate discrimination between benign and malignant renal cell tumors (RCTs) as well as among malignant RCTs, owing to differential risk of progression through metastization. Although histone methylation has been implicated in renal tumorigenesis, its potential as biomarker for renal cell carcinoma (RCC) progression remains largely unexplored. Thus, we aimed to characterize the differential expression of histone methyltransf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 55 publications
1
14
1
Order By: Relevance
“…Indeed, inactivation of this histone-modifying enzyme results in increased tumor progression and aggressiveness, and poorer patient outcome [93]. To illustrate the different epigenetic background in the heterogeneity of RCC, a set of histone methyltransferases and demethylases is able to accurately discriminate among the various RCC subtypes and oncocytoma, an important differential diagnosis [94]. Also, several promoter-methylated genes involved in the various hallmarks of cancer are found in RCC, including the ones related to angiogenesis (in which VHL is included), metabolism, apoptosis and cell cycle, among others [95].…”
Section: Role Of Immunoepigenetics?mentioning
confidence: 99%
“…Indeed, inactivation of this histone-modifying enzyme results in increased tumor progression and aggressiveness, and poorer patient outcome [93]. To illustrate the different epigenetic background in the heterogeneity of RCC, a set of histone methyltransferases and demethylases is able to accurately discriminate among the various RCC subtypes and oncocytoma, an important differential diagnosis [94]. Also, several promoter-methylated genes involved in the various hallmarks of cancer are found in RCC, including the ones related to angiogenesis (in which VHL is included), metabolism, apoptosis and cell cycle, among others [95].…”
Section: Role Of Immunoepigenetics?mentioning
confidence: 99%
“…The expression of SETDB2 in CD34+/CD38cells isolated from AML1-ETO positive cases (n = 10) was significantly higher than that in healthy human CD34 +/CD38 cells ( Figure 1A). In addition, SETDB2 expression in t(8;21) positive AML was significantly higher than that in normal bone marrow CD34+ cells, PML-RARa, inv (16) and FLT3-ITD positive AML cases ( Figure 1B). In the AML cell lines, we also found that SETDB2 expression was significantly higher in t(8;21) positive AML cells than in other t(8;21) negative AML cells ( Figure 1C).…”
Section: Expression Of Setdb2 In Aml1-eto Positive Aml Patientsmentioning
confidence: 94%
“…The CD34+CD38cells were used to detect the expression of SETDB2. The second sample cohort included bone marrow tissue of 13 normal healthy individuals and 96 AML patients collected from June 2017 to June 2018 (including t(8; 21), n = 56; pML-RARa, n = 25; inv (16), n = 15), used to isolate mononuclear cells for detection of SETDB2 expression; the third sample cohort included 42 patients with AML1-ETO negative and 50 patients with AML1-ETO positive AML from June 2013 to June 2018. These cases contain patient survival data.…”
Section: Human Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cancer Genome Atlas (TCGA) ( http://cancergenome.nih.gov/ ) is a database of expression profiles for at least 30 kinds of cancers, including prostate cancer [ 25 27 ]. TCGA can be used to explore clinicopathological parameters associated with patients with cancer, which were used in this study [ 28 , 29 ]. In the current study, the RNA sequencing (RNA-Seq) data for prostate cancer patients, which were taken from the Illumina MiSeq RNA-Seq platform, contained 498 prostate cancer cases and 52 normal prostate cases, up to 1st November 2017.…”
Section: Methodsmentioning
confidence: 99%